Cegah Bullying Sejak Dini: Edukasi Partisipatif Mahasiswa KPM UNSIQ di SDN Guyangan Purworejo (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2026)
Bullying is a serious problem in elementary schools that negatively impacts student mental health and achievement. The 2026 UNSIQ Student Community Service Program (KPM) implemented anti-bullying education at Guyangan Elementary School, Purworejo, using a participatory educational approach through literacy, creativity, and counseling. This activity targeted all students and teachers, using observation, documentation, and interviews. Results showed an increase in students' understanding of the meaning, forms, and impacts of bullying, as well as a growing awareness, empathy, and mutual respect. This approach effectively creates a safe and inclusive school environment while strengthening character education. This activity was carried out through various methods, including observation, documentation, and interviews. By involving the active participation of students and teachers, it is hoped that they will better understand the meaning of bullying, recognize its various forms, and realize its negative impact on individuals and the school environment. Through literacy, students are encouraged to dig deeper into bullying, while through creativity, they are given space to create solutions and anti-bullying campaigns in schools. Counseling was conducted to strengthen their understanding of the importance of mutual respect and empathy..